AB0307 DOES FCGR2A, FCGR3A AND FCGR3B POLYMORPHISM CAN PREDICT ANTI-DRUG ANTIBODIES APPARITION IN RHEUMATOID ARTHRITIS PATIENTS TREATED WITH TNF-BLOCKERS?. (2nd June 2020) - Mahmoud, I.; Moalla, M.; Ben Tekaya, A.; Bouden, S.; Tekaya, R.; Saidane, O.; Sfar, I.; Gorgi, Y.; Abdelmoula, L.
Abstract : Background: Fc gamma receptors (FcγRs) play a major role in the regulation of humoral immune responses. Single-nucleotide polymorphisms (SNPs) of FCGR2A and FCGR3A and FCGR3B can impact the expression level, IgG affinity and function of the CD32 and CD16 FcγRs in response to their engagement by the Fc fragment of IgG. It was described in patient treated for rheumatoid arthritis (RA), that such a polymorphism may influence patients response to TNF-blockers. Objectives: In this study, we aimed to investigate whether the FCGR2A H131R (rs1801274), FCGR3A F158V (rs396991), and FCGR3B NA1/NA2 polymorphisms can be involved in the genesis of anti-drug-antibody ADAb to anti-TNF therapy in RA patients under etanercept (ETA), adalimumab (ADL) and infliximab (INF). Methods: We included 47 patients treated for RA under TNF-blockers. To assess the association between the FCGR2A H131R (rs1801274), FCGR3A F158V (rs396991), and FCGR3B NA1/NA2 polymorphisms and immunogenicity of TNF-blockers, we used allele contrast, the recessive model, the dominant model, and the homozygote contrast. Quantitative measurements of the ADAbs was carried out by a commercial enzyme-linked immunosorbent assay (ELISA) kit (Promonitor) ® after 6 months of treatment. Results: We involved 18 patients treated with ETA, 13 patients with ADL and 16 under INF. None of the patients under ETA has developed ADAb and respectively 1 and 7 patients developed immunogenicity with ADL and INF. We excluded patients under ETA from statistical study since they didn't develop ADAb. A significant association was revealed between FCGR2A H131R polymorphism and immunogenicity of INF and ADL (table 1 ). Conclusion: FCGR2A R allele carriers show less susceptibility to develop ADAb to ADL and INF with follow-up times of 6 months. Our results provide an explanation for controversies in the relationships between FCGR2A H131R polymorphism and TNF-blockers response. Further studies with larger population of RA patients should be undertaken to confirm this hypothesis. References: None Disclosure of Interests: None declared